2021
DOI: 10.1136/postgradmedj-2021-140829
|View full text |Cite
|
Sign up to set email alerts
|

Are family medicine residents trained to counsel patients on physical activity? The Canadian experience and a call to action

Abstract: Physical inactivity is a leading risk factor for non-communicable diseases (NCDs) and early mortality. Family physicians have an important role in providing physical activity counselling to patients to help prevent and treat NCDs. Lack of training on physical activity counselling is a barrier in undergraduate medical education, yet little is known regarding physical activity teaching in postgraduate family medicine residency. We assessed the provision, content and future direction of physical activity teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…[ 77 ] reported that primary care physicians do not have sufficient time to discuss preventive care with their patients, spending only 29 min per working day on discussing preventive care, when they needed 6.1 h [ 77 ]. Moreover, lack of training in PA counseling among medical graduates and primary care providers is a barrier to promoting PA in primary care [ 78 , 79 , 80 , 81 , 82 ]. Primary care providers may have limitations to comprehensively counsel their patients about PA in such a time-limited encounter.…”
Section: Referral To Physical Activity Resources and Professionalsmentioning
confidence: 99%
“…[ 77 ] reported that primary care physicians do not have sufficient time to discuss preventive care with their patients, spending only 29 min per working day on discussing preventive care, when they needed 6.1 h [ 77 ]. Moreover, lack of training in PA counseling among medical graduates and primary care providers is a barrier to promoting PA in primary care [ 78 , 79 , 80 , 81 , 82 ]. Primary care providers may have limitations to comprehensively counsel their patients about PA in such a time-limited encounter.…”
Section: Referral To Physical Activity Resources and Professionalsmentioning
confidence: 99%
“…[3] Additionally, it can assist in lowering the risks of early mortality, coronary heart disease, strokes, high blood pressure, obesity, and non-communicable diseases (NCDs). [4][5][6] On the other hand, physical inactivity and sedentary behavior are major public health concerns, particularly among young adults like college students who struggle to balance academic, work, and personal responsibilities. In Saudi Arabia, physical inactivity is prevalent among both middle-aged and young individuals from diverse ethnic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Additionally, it can assist in lowering the risks of early mortality, coronary heart disease, strokes, high blood pressure, obesity, and non-communicable diseases (NCDs). [4–6]…”
Section: Introductionmentioning
confidence: 99%